(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In this paper we give the main uses of wavelets in statistics, with emphasis in time series analysis. We include the fundamental work on non parametric regression, which motivated the development of techniques used in the estimation of the spectral density of stationary processes and of the evolutionary spectrum of locally stationary processes.